Serotonin acts through YAP to promote cell proliferation: mechanism and implication in colorectal cancer progression - Huangfei Yu; Tianyin Qu; Jinlan Yang; Qing Dai (Cell Communication and Signaling, 2023)
Abstract Serotonin, also known as 5-hydroxytryptamine (5-HT), is a key messenger that mediates several central and peripheral functions in the human body. Emerging evidence indicates that serotonin is critical in tumorigenesis, but its role in colorectal cancer remains elusive. Herein, we report that serotonin transporter (SERT) transports serotonin into colorectal cancer cells, enhancing Yes-associated protein (YAP) expression and promoting in vitro and in vivo colon cancer cell growth. Once within the cells, transglutaminase 2 (TG2) mediates RhoA serotonylated and activates RhoA-ROCK1/2 signalling to upregulate YAP expression in SW480 and SW1116 cells. Blocking SERT with citalopram reversed the serotonin-induced YAP expression and cell proliferation, inhibiting serotonin’s effects on tumour formation in mice. Moreover, SERT expression was correlated with YAP in pathological human colorectal cancer samples and the levels of 5-HT were highly significant in the serum of patients with colorectal cancer. Together, our findings suggested that serotonin enters cells via SERT to activate RhoA/ROCK/YAP signalling to promote colon cancer carcinogenesis. Consequently, targeting serotonin-SERT-YAP axis may be a potential therapeutic strategy for colorectal cancer. Video abstract